Tigers of Lanka, from boys to guerrillas - Narayan Swamy, M. R. (Delhi : Konark Publishers, 2002)
Study of Tamil militancy in Sri Lanka
Includes index
Keywords: Tamilila Vitutalaippulikal (Association) -- History; Tamil (Indic people) -- Sri Lanka -- Politics and government; Subversive activities -- Sri Lanka; Sri Lanka -- Politics and government